Wavelength considerations in confocal microscopy of botanical specimens - Fricker, M; White, N (Wiley, 1992)
We have used a multiple-laser confocal microscope with lines 325, 442, 488, 514 and 633 nm to investigate optical sectioning of botanical specimens over a wide range of wavelengths. The 442-nm line allowed efficient excitation of Chromomycin A3, with minimal background autofluorescence, to visualize GC-rich heterochromatin as an aid to chromosome identification. Sequential excitation with 442- and 488-nm light enabled ratio imaging of cytosolic pH using BCECF. The red HeNe laser penetrated deep into intact plant tissues, being less prone to scattering than shorter blue lines, and was also used to image fluorescent samples in reflection, prior to fluorescence measurements, to reduce photobleaching. Chromatic corrections are more important in confocal microscope optics than in conventional microscopy. Measured focus differences between blue, green and red wavelengths, for commonly used objectives, were up to half the optical section thickness for both our multi-laser system and a multi-line single-laser instrument. This limited high-resolution sectioning at visible wavelengths caused a loss in signal. For ultraviolet excitation the focus shift was much larger and had to be corrected by pre-focusing the illumination. With this system we have imaged DAPI-stained nuclei, callose in pollen tubes using Aniline Blue and the calcium probe Indo-1.